Identification of Antibacterial Compounds in Methanol Extract of Clove Stems (Syzygium aromaticum) using Liquid Chromatography Mass Spectrometry - Yunita Diyah Safitri; Rahma Diyan Martha; Mutia Hariani Nurjanah (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Clove is well-known as an herbal plant that is also included in the spice group which is known to have an antibacterial activity spread across the stems, leaves, and flowers. Objectives: The purpose of this study was to identify the antibacterial compounds that are found in the methanol extract of clove stems and the antibacterial activity of clove stem extract against Bacillus cereus. Methods: We used Liquid Chromatography Mass Spectrometry (LC-MS) method to identify the antibacterial compounds, and used the paper disc method (Kirby Bauer) for antibacterial test with clove stem extract concentrations of 30%, 50%, and 70%, positive control of Amoxicillin at a dose of 0.5 mg/ml, also a negative control of sterile aquadest. Results: The results showed four antibacterial compounds in the extract, namely (+)-Licarin A, 4-O-Caffeoylquinic acid_1, Eckol, and Leucodelphinidin. Methanol extract of clove stems at the concentrations of 30%, 50%, and 70% inhibited the growth of Bacillus cereus significantly (p <0.05). The concentration of 30% was categorized as quite sensitive, meanwhile, both 50% and 70% were categorized as sensitive. Conclusions: In conclusion, four compounds with antibacterial properties were found in the methanol extract of clove stems based on LCMS analysis, and supported by the results of antibacterial tests which showed the formation of an inhibition zone in the clove stem extract against the growth of Bacillus cereus.